The Evangelical Puzzle Partially Explained: Privileged Prejudice and the Development of Appreciative Attitudes Toward Evangelical Christianity - Mayhew, Matthew J.; Winkler, Christa E.; Staples, B. Ashley; Singer, Kevin; Shaheen, Musbah; Rockenbach, Alyssa N. (Frontiers in Education, 2022)
Background: Evangelical Christian college students simultaneously experience the privileges that accompany dominant religious identities and feel a need to conceal their identity and perspectives on college campuses. Consistently and empirically, the college campus has been studied for its potential to help students develop appreciative attitudes toward religious, secular, and spiritual worldviews. Yet, few studies have investigated evangelical Christian appreciation longitudinally over 4 years of college, and even fewer through the additional use of a mixed-methods design. Purpose: This inquiry examined if and how college students developed an appreciation of evangelical Christianity over 4 years of college. Methods: This paper used data gathered through the Interfaith Diversity Experiences and Attitudes Longitudinal Survey (IDEALS), a nationally-representative, mixed-methods study that included survey data collection from 9,470 students at 122 colleges and universities over 3 time points, and 18 qualitative case studies conducted across institutions of various sizes, locations, and affiliations. Results: Using latent growth modeling, we demonstrated that overall appreciation for evangelical Christianity developed during college and was related to institutional cultures that invited and embraced worldview diversity as well as religiously-inclusive campus climates and practices. Related qualitative insights storied change in evangelical appreciation that centered on personal relationships with evangelicals, efforts to understand evangelical viewpoints, and a recognition that Christian students often have the privilege of operating from unexamined beliefs. Conclusion and Implications: Study results provide recommendations for educational practices that support student growth from tolerance to appreciation for evangelical Christianity.